Leaderless foot-and-mouth disease virus serotype O did not cause clinical disease and failed to establish a persistent infection in cattle - Benedikt Litz; Julia Sehl-Ewert; Angele Breithaupt; Anja Landmesser; Florian Pfaff; Aurore Romey; Sandra Blaise-Boisseau; Martin Beer; Michael Eschbaumer (Emerging Microbes and Infections)
The foot-and-mouth disease virus (FMDV) Leader proteinase Lpro inhibits host mRNA translation and blocks the interferon response which promotes viral survival. Lpro is not required for viral replication in vitro but serotype A FMDV lacking Lpro has been shown to be attenuated in cattle and pigs. However, it is not known, whether leaderless viruses can cause persistent infection in vivo after simulated natural infection and whether the attenuated phenotype is the same in other serotypes. We have generated an FMDV O/FRA/1/2001 variant lacking most of the Lpro coding region (ΔLb). Cattle were inoculated intranasopharyngeally and observed for 35 days to determine if O FRA/1/2001 ΔLb is attenuated during the acute phase of infection and whether it can maintain a persistent infection in the upper respiratory tract. We found that although this leaderless virus can replicate in vitro in different cell lines, it is unable to establish an acute infection with vesicular lesions and viral shedding nor is it able to persistently infect bovine pharyngeal tissues.